Impact of networking capability on organizational survival of SMEs: Mediating role of strategic renewal - Hassan Ahmed Shah; Muhammad Yasir; Abdul Majid; Asad Javed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
Organizational survival (OS) is still in spotlight in management literature because of the threats posed by the uncertain and volatile business environment across the globe. Fierce competition among organizations and unstable business environment has made organizations to focus on their survival in first place. The main purpose of this study is to examine the role of networking capability (NC) having four dimensions i.e. coordination (CO), relational skills (RS), partner's knowledge (PK), and internal communication (IC) of a firm in the assurance of its survival. The mediating role of strategic renewal (SR) in these relationships is also investigated. For testing these relationships, data was gathered from 469managers/owners of small and medium enterprises (SMEs) and was analyzed accordingly. Besides descriptive analysis, correlations, and regression, mediation analysis were carried out by using Baron and Kenny's approach and PROCESS Macros. The results proved that CO, RS, PK, and IC have significant positive impact on OS. Moreover, SR also has strong mediating effect on the relationships between NC and OS. This study has some meaningful contributions towards both theoretical and practical knowledge of the subject matter.
Keywords: 330; networking capability; strategic renewal; organizational survival; and small and medium enterprises; SMEs